228k views
0 votes
Please helpppp!! with the answers below which option is correct

Please helpppp!! with the answers below which option is correct-example-1

2 Answers

5 votes
11 √3–7 √6

Look how I solve it :

7√3–4√6+√48–√54
=7√3–4√6+ √3*16–√9*6
=7√3–4 √6+4√3–3√6
=11√3–7√6
User Dave
by
4.9k points
4 votes
We can simplify the √48 and the √54

√48 = √16*3 = 4√3
√54 = √9*6 = 3√6

now combine with the other two terms:

(7+4)√3 - (4+3)√6 = 11√3 - 7√6

That's answer B.


User Brad Heller
by
5.7k points